Biostratigraphy of the Jurassic strata in the Dutch Central North Sea Graben - Herngreen, G.F.W; Lissenberg, Th; White, L.J (Danmarks Geologiske Undersøgelse Serie B, 1991)
This contribution presents an extended abstract intended for the proceedings of the symposium: The Jurassic in the southern Central Graben, Hørsholm (Denmark) June 15-16, 1989. The full text entitled "Dinoflagellate, sporomorph, and micropaleontological zonation of Callovian to Ryazanian strata in the Central North Sea Graben, The Netherlands" has been published in the proceedings of the 2nd International Symposium on Jurassic Stratigraphy, Lisbon 1989, p. 745-762.